Behavior of Overcoming graduate degree in nursing Cienfuegos - Vladimir Barco Díaz; Zoraida Caridad Álvarez Figueredo; Yusimy Miranda Pérez; Juan Carlos Alvarado Peruyero; Esteban Jesús Sánchez Martínez (Medisur)
Background: Graduate overcoming represents the continuous process to achieve the updated development of professionals. Objective: To determine the behavior of overcoming graduate degree in nursing from Cienfuegos. Methods: A retrospective descriptive study of 72 nursing graduates working in Primary Health Care, selected by random combination, first each of the areas of health was considered a stratum and then the professionals were selected by simple random method. We included the years from 2000 to 2008. A survey that collected the variables: years of graduate, postgraduate courses received, amount of research, publication of research and scientific events that have participated over the eight years studied. Results: More than a third made no postgraduate course or other form of improvement over the eight years studied. Almost half did not conduct scientific research and those who did not perform more than three investigations. Half did not participate in any scientific event. Conclusions: Overcoming graduate nursing graduates working in Primary Health Care in Cienfuegos municipality is insufficient.